Асаблівасці дыялектных назваў населеных пунктаў Сакольскага павета (па матэрыялах да Слоўніка геаграфічных назваў поўночна-ўсходняй Польшчы) - Tratsiak, Volha (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
In the article there are 222 place names of Sokolka district registered in dialectal variants. The material used for the study constituted survey manuscripts made for The Dictionary Of North- Eastern Poland Place Names, which were collected by a team of philologists, leaded by Professor Antonina Obrebska-Jablonska, arranged by the Commission of Determining the Place and Object Names at the Office of the Council of Ministers of the Republic of Poland in 1961–1970. Dialectal forms of oyconyms analysis was carried out on three levels: structural, phonetic and formative. The study shows that the dialectical variants of place names of the Sokolka district, registered in source materials, were used by the inhabitants of the test area, in spoken variants maintaining phonetic and morphological characteristics typical for the dialect of the test area. Particular impact on dialect variants of names had Belarusian language and its dialects. These influences were primarily observed at the level of phonetics: variable accent, vowel reduction, a diphtong like pronunciation of certain vowels et al. However, at the formative level, the big influence on the construction of oyconyms models had also other East Slavic languages.